A Highly Efficient Coordination Polymer for Selective Trapping and Sensing of Perrhenate/Pertechnetate - Li, Cheng-Peng; Zhou, Hang; Chen, Jing; Wang, Jia-Jun; Du, Miao; Zhou, Wuzong (ACS applied materials & interfaces, 2020)
A porous cationic Ag(I) coordination polymer, [Ag(1,2,4,5-p4b)](SbF ) (TJNU-302) with the ligand 1,2,4,5-p4b (1,2,4,5-tetra(pyridin-4-yl)benzene), is reported that shows high sorption capacity (211 mg g ) and distribution coefficient (5.8 × 10 mL g ) as well as outstanding selectivity in 500 times excess of CO or PO anion for perrhenate removal. TJNU-302 can act as a crystalline turn-off sensor for perrhenate upon UV radiation. In this way, a test paper strip for sensing ReO could be produced. In water solution, TJNU-302 shows an efficient fluorescence quenching response to ReO ion, with the highest quenching percentage (86%) among all reported ReO sensors. These results could be elucidated by the bonding properties of single-crystal structures of TJNU-302 before and after perrhenate sorption, as well as density functional theory (DFT) calculations.